2020
DOI: 10.1021/acs.jafc.0c01997
|View full text |Cite
|
Sign up to set email alerts
|

Natural Melanin Produced by the Endophytic Bacillus subtilis 4NP-BL Associated with the Halophyte Salicornia brachiata

Abstract: Natural melanin with many interesting properties has potential applications in cosmetics, drug delivery, semiconductors, etc. However, conventional production methods are not efficient, resulting in its high cost (350−650 USD g −1 ), which has been a bottleneck for its efficient commercial utilization. To explore a faster extraction method with a higher yield, a melanin-producing endophytic bacterium was isolated from the halophyte Salicornia brachiata and further identified as Bacillus subtilis 4NP-BL by phyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 50 publications
0
32
0
Order By: Relevance
“…The molecular structure of melanins includes multiple different reactive functional groups (−OH, −NH, and −COOH) [21]. They can be obtained and have been characterized by a variety of natural sources, including animals, plants, bacteria, and fungi [10,11,33,34]. Importantly, melanins are multifunctional and biologically-active, natural macromolecules and can be characterized as antioxidant, radioprotective, thermo-regulative, chemoprotective, antitumor, antiviral, antimicrobial, immunostimulating and/or anti-inflammatory [10,32,[34][35][36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular structure of melanins includes multiple different reactive functional groups (−OH, −NH, and −COOH) [21]. They can be obtained and have been characterized by a variety of natural sources, including animals, plants, bacteria, and fungi [10,11,33,34]. Importantly, melanins are multifunctional and biologically-active, natural macromolecules and can be characterized as antioxidant, radioprotective, thermo-regulative, chemoprotective, antitumor, antiviral, antimicrobial, immunostimulating and/or anti-inflammatory [10,32,[34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, melanins, like biopolymers, are obtained from renewable resources and are non-toxic; these two features make their use "greener" than many existing commercial additives [35]. Importantly, large-scale production of melanins by microorganisms digesting food waste, as well as by sustainable extraction from natural plant-residues (e.g., watermelon seeds) have been demonstrated [10,11,34]. In fact, melanin from watermelon seeds has been shown to have antioxidant and UV-barrier properties [10].…”
Section: Introductionmentioning
confidence: 99%
“…10 The ratio of A650/A500 helps to calculate the amount of eumelanin in the total melanin. 23 The ratio A650/A500 was calculated to be 0.35 and indicated that extracted melanin was belonging to eumelanin class whereas, a ratio below 0.15 is observed for pheomelanin.…”
Section: Uv/vis Spectrophotometrymentioning
confidence: 99%
“…The effect of the medium components on melanin production was quantified by measuring the absorbance of the respective culture supernatants at 400 nm. 23…”
Section: Medium Optimization For Melanin Production 2331 One Factor At a Time (Ofat)mentioning
confidence: 99%
See 1 more Smart Citation